The case of diagnostics of invasive pulmonary aspergillosis by in vivo probe-based confocal laser endomicroscopy of central and distal airways - Danilevskaya, Olesya (Elsevier, 2014)
We present a case of 41-year-old patient with invasive pulmonary aspergillosis (IPA) in which probe-based confocal laser endomicroscopy (pCLE) imaging of central and distal airways was first performed in vivo. pCLE imaging showed the signs of complete or partial destruction of elastin network of alveolar wall with fibrillar branching fluorescent structures in the zone with typical IPA changes on HRCT.